Buddhist Philosophy, Mental Well-being, and the Pursuit of Peace in a Chaotic World - Saingjamsai, Phra Amnaj Tachapunyo; Saysook , PhraNarong Suphatto; Khammuangsaen, Boonruam (Journal of Dhamma for Life, 2025)
The study found that Buddhism views mental well-being as a state of inner peace, free from internal conflicts, and guided by wisdom. Key Buddhist principles related to mental well-being include the Four Noble Truths, which explain the causes of suffering and the path to its cessation, the Three Characteristics of Existence (Tilakkhaṇa), which help individuals understand impermanence, reduce attachment, and alleviate suffering caused by clinging to worldly matters, and the Four Divine Abidings (Brahmavihāra) loving-kindness (mettā), compassion (karuṇā), sympathetic joy (muditā), and equanimity (upekkhā) which contribute to emotional balance and harmonious social relationships. Additionally, mindfulness, concentration, and insight meditation play crucial roles in enhancing mental well-being. Mindfulness helps individuals regulate emotions and approach challenges with calmness, concentration reduces mental distractions and strengthens inner stability, while insight meditation cultivates wisdom that leads to a deeper understanding of life’s reality. By applying these Buddhist philosophical principles appropriately, individuals can develop a stable mental well-being and attain peace despite the complexities of modern society. Furthermore, Buddhist philosophy provides a structured approach to managing emotional challenges and stress in contemporary life. The Noble Eightfold Path, which encompasses morality (sīla), concentration (samādhi), and wisdom (paññā), offers a comprehensive guide for cultivating right understanding, mindful living, and ethical behavior that promotes mental well-being. Living in accordance with Buddhist principles not only reduces suffering and enhances happiness but also fosters balanced relationships and enables individuals to navigate the chaos of the modern world with peace and clarity.